Big Data Analysis on Indonesia’s Primary Care Pay-For Performance - Darmasurya, Aditya; Aryani, Ari Dwi; Ritonga, Rahmad Asri; Anindita, Rahma; Tsani, Pranatawati Nur; Yudanto, Bayu; Trisnanto, Tedo Arya; Trisnasari, Trisnasari (UI Scholars Hub, 2024)
In Indonesia’s social security program (JKN), there are more than 1,6 million visits in primary care providers each day. Indonesia's Social Security Administrative Body for Health (BPJS Kesehatan) manages the healthcare data recorded by the providers. In late 2019, the new Performance-Based Capitation (KBK) was introduced to primary care providers. They are assessed every month before the due for capitation payment. There are three indicators in the KBK scheme which are contact rate, non-specialty referral ratio, and proportion of PROLANIS disease management program members with controlled clinical outcome (PROLANIS indicator. This study analyzes data insights of KBK through big data analysis to determine whether the policy shows improvement of primary care providers. It is a non-experimental big-data analysis by observational descriptive method. Data was retrieved from BPJS Kesehatan Business Intelligence program. There has been improvement in the indicator target achievement every year. However, only non-specialty referral ratio has reached the intended target. In July 2024, contact rate reached 149,56%, non-specialty referral ratio reached 0,85%, and PROLANIS indicator reached 4,71%.. KBK data shows the policy has improved quality of primary care providers. Further collaboration among all stakeholders is needed to increase the achievement.